(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
For the concurrent measurement of Dapagliflozin Propanediol Monohydrate (DAPA) and Metformin Hydrochloride (MET) in combined dosage form, a quick, accurate, specific and easy Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) approach was created. The method was performed on a column C8 RRHD Eclipse (150 × 4.60 mm, 5 µm). 5 mM Ammonium Acetate Buffer pH-4.0, Methanol and Acetonitrile were the components of the mobile phase in the ratios of 30:65:05, respectively. The effluent was detected at 227 nm at a flow rate of 0.4 mL/min. The observed retention times for DAPA and MET were 7.297 and 3.230 min, respectively. The drug was stressed by being exposed to acid and alkali hydrolysis. From the mass spectra, it was found that two degradant peaks were observed in the standard mixture and the sample during alkali stress condition and probable degradants formed. The developed approach was validated in accordance with ICH guidelines. With correlation coefficients of 0.9969 for DAPA and 0.9975 for MET, it was discovered that the standard curve was linear over the range of 60-140 µg/mL and 300-700 µg/mL for DAPA and MET, respectively. The limit of detection (LOD) was 2.959 µg/mL and 8.893 µg/mL for DAPA and MET, respectively. The limit of quantification (LOQ) was 8.967 µg/mL and 26.949 µg/mL for DAPA and MET, respectively. The % recovery was determined in between 98 to 102%. The precision was within the limit (Relative Standard Deviation (RSD) <2%). The proposed stability indicating LC-MS/MS method can be successfully utilized for simultaneous estimation of DAPA and MET in combined dosage form without any prior separation of individual drugs and no interference was found due to degradant formed during stress condition.